2001
DOI: 10.1016/s0167-4889(01)00087-8
|View full text |Cite
|
Sign up to set email alerts
|

Multipathways for transdifferentiation of human prostate cancer cells into neuroendocrine-like phenotype

Abstract: The neuroendocrine (NE) cell is a minor cell population in normal human prostate glands. The number of NE cells is increased in advanced hormone-refractory prostate carcinomas (PCA). The mechanism of increased NE cell population in these advanced tumors is poorly understood. We examined molecular mechanisms which may be involved in the regulation of the transdifferentiation process of human PCA cells leading to a NE phenotype. We compared PCA cell lines LNCaP and PC-3 in the following medium conditions: steroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 61 publications
7
76
0
1
Order By: Relevance
“…The initial study revealed that androgensensitive (AS) LNCaP cells exhibit the capability of being transdifferentiated into an NE-like phenotype in response to androgen deprivation (Shen et al 1997). Our data further showed that androgenreduced media can induce NE transdifferentiation of AS LNCaP cells, and these cells acquire the neuronal phenotype and express multiple NE markers, including NSE, CgA, gastrin, and neurotensin (Zelivianski et al 2001, Yuan et al 2006. This NE transdifferentiation induced by steroidreduced (SR) medium is reversed by the addition of DHT.…”
Section: Multipathways Involved In Ne Transdifferentiation Of Pca Celmentioning
confidence: 64%
See 1 more Smart Citation
“…The initial study revealed that androgensensitive (AS) LNCaP cells exhibit the capability of being transdifferentiated into an NE-like phenotype in response to androgen deprivation (Shen et al 1997). Our data further showed that androgenreduced media can induce NE transdifferentiation of AS LNCaP cells, and these cells acquire the neuronal phenotype and express multiple NE markers, including NSE, CgA, gastrin, and neurotensin (Zelivianski et al 2001, Yuan et al 2006. This NE transdifferentiation induced by steroidreduced (SR) medium is reversed by the addition of DHT.…”
Section: Multipathways Involved In Ne Transdifferentiation Of Pca Celmentioning
confidence: 64%
“…In addition to the regulation of integrin signaling and potassium channel activity, RPTPa plays a critical role in neuronal differentiation (Pallen 2003). In AS LNCaP cells, the expression of RPTPa at both mRNA and protein levels is upregulated by androgen depletion, correlating with NE differentiation and NSE expression (Zelivianski et al 2000(Zelivianski et al , 2001. Furthermore, addition of androgens abolishes steroid depletion-induced RPTPa elevation, while Casodex can compete out androgen effects and restores RPTPa as well as NSE expression (Zhang et al 2003).…”
Section: Mechanisms Of Androgen Depletion-induced Ne Differentiationmentioning
confidence: 99%
“…Physiological Implication of Voltage-dependent Calcium Channels-To identify the putative involvement of T-type calcium channels in prostate cell physiology, we first studied the influence, on voltage-dependent calcium currents, of steroid reduction, previously reported to induce neuroendocrine differentiation (10,11). Indeed, LNCaP cells cultured in steroidreduced conditions displayed a morphological differentiation as shown on Fig.…”
Section: The ␣ 1h T-type Calcium Channel Is Involved In a Window Calcmentioning
confidence: 99%
“…The stimulation of neuroendocrine differentiation by interleukin 6 has been shown to involve the induction of cyclin-dependent kinase inhibitor p27 Kip1 (7), as well as the tyrosine phosphorylation of epithelial and endothelial tyrosine kinase Etk/ Bmx through the activation of phosphatidylinositol 3Ј-kinase (6). Steroid removal from the culture medium was also shown to induce neuroendocrine differentiation (10,11).…”
mentioning
confidence: 99%
“…The NE-like LNCaP cells grown under steroid-reduced conditions have been shown to express androgen receptor. 16 It was possible to reverse the NElike phenotype after 1 month by changing the media to normal serum. However, beyond 3 months in media containing charcoal-stripped serum, the cell morphology could not be reversed.…”
Section: Growth Of Lncap Cells In Charcoal-stripped Media or Casodex mentioning
confidence: 99%